What is a glide path? - Sachin Passi; Nisha Kaler; Nandini Passi (Wolters Kluwer Medknow Publications, 2016)
Three-dimensional cleaning, shaping, and obturation of root canal system can be considered as foundations for a predictable endodontic success. One guiding strategy that has emerged as a critical part of endodontic success is the creation and maintenance of a glide path. Without it, cleaning and shaping become unpredictable because there is no guide for endodontic mechanics. Thus, a smooth glide path is the secret to safe and successful rotary shaping. However, this subject of glide path has no formal training in the endodontic curricula in most of the dental schools worldwide. The purpose of this review article is to serve as a reference guide for endodontic glide path preparation. Knowing what to do is only half of the job, implementing different skills in day-to-day clinical practice will accomplish the job fully, ensuring successful endodontic treatment outcomes.